An experimental study to evaluate the performance of stone mastic asphalt mixtures - Foo, Si Mian. (2010)
Since the 1960s, Stone Mastic Asphalt (SMA) pavement surfaces have been used successfully in Germany on heavily trafficked roads. Due to its excellent performance characteristics, road authorities in Germany and other major European countries soon adopted SMA as a standard wearing course. Since then, SMA has spread and gained acceptance all over the world.